The Implementation of Promotional Strategies via TikTok Social Media in Increasing Sales Revenue at Fat Hunt Surabaya - Ossa Yuansah Putri; Yanda Bara Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research discusses how digital promotion strategies through the TikTok platform can be effectively implemented to increase sales turnover in micro, small and medium enterprises (MSMEs). This research approach is descriptive qualitative with data collection techniques through interviews with owners, employees, and consumers. The results showed that the implementation of promotional strategies was carried out through optimizing TikTok accounts, creating attractive visual content, collaborating with influencers, and active and responsive interaction with audiences. This strategy is reinforced by a personalized approach through comment replies and direct communication relevant to customer needs. Turnover data shows a significant increase from November 2024 to April 2025, with the highest figure reaching Rp 70,000,000. This finding shows that a promotional strategy that is carried out creatively, and consistently is able to increase the competitiveness of MSMEs and encourage increased sales in a business.